СOMPLICATIONS OF ENDODONTIC TREATMENT: PECULIARITIES OF CLINICAL SIGNS, DIAGNOSIS - O.V. Hurzhii; S.V. Kolomiiets (Ukrainian Medical Stomatological Academy, 2018)
Endodontic lesions take leading positions in the structure of modern dentistry. General areas of the displacement of filling material or instruments because of the poor quality of endodontic treatment have been established, and the features of clinicoroentgenological and neurological manifestations of the complications of endodontic dentistry have also been determined. Due to the poor quality of endodontic treatment, general areas of the displacement of filling material or instruments have been identified, they are the mandibular canal, the maxillary sinus and periapical bone tissue. We have performed the examination of 32 patients with various complications after endodontic treatment during 2017 to 2018. The majority of patients were adults - 28(87,5%), over the age of 60 - 4(12,5%), there were 84,4% females and 15,6% males within the group. The patients were divided into 3 groups according to localization of foreign bodies: the first group contained patients with foreign bodies present in the area of mandibular canal - 5(15,6%); the patients represented by the material in the maxillary sinus cavity made up the second group - 9(28,1%); the group of patients whose material was localized behind the tooth apex in the bone tissue included 18(56,2%)persons. The greatest number of complications after endodontic therapy was observed during the treatment of molars- 67,9%. Duration of disease (from the end of endodontic treatment to the hour of addressing the clinic) varied from 1 to 6 months. For the purpose of identification, the foreign material localization along with traditional clinic examination, which includes complaints analysis, anamnesis data, estimation of general health status and local manifestations of the disease, the dental intraoral X-ray, plain roentgenography and computed tomography of the bones of the jaws were performed. Assessment of the tissues sensitivity was conducted by the method of comparative palpation of the skin and mucosa at the areas of innervation of the trigeminal nerve branches. As a result of the investigation we have determined that regardless of exact localization of the foreign material, surgical complications after endodontic treatment were always accompanied with pain syndrome of different intensity, reduction of sensitivity during the placement of the filling material in the area of mandibular canal (extra- or intracanal), signs of inflammation development (bounded or generalized adjacently to mucosa of maxillary sinus) or persistent pain syndrome during displacement of filling material into the bone tissue behind the tooth apex. To specify areas and borders of the localization of the foreign body, the findings of the roentgenological investigations, in particular computed tomography, were critical.